Assessing hemorrhagic risks in combination therapy: implications of angiogenesis inhibitors and immune checkpoint inhibitors - Yuhui Yang; Yuhui Yang; Yuhui Yang; Pingping Long; Pingping Long; Ying Tuo; Ying Tuo; Xiaoxiao Wang (Frontiers in Immunology)
ObjectiveThis study aims to evaluate the hemorrhage risk in solid tumor patients receiving angiogenesis inhibitors (AGIs), immune checkpoint inhibitors (ICIs), and their combination using the FDA Adverse Event Reporting System (FAERS) database.MethodsData from Q1 2011 to Q4 2023 were extracted from the FAERS database for solid tumor patients treated with AGIs, ICIs, or their combination. A disproportionality analysis was conducted by calculating the reporting odds ratio (ROR) and corresponding 95% confidence interval (CI), as well as the Proportional Reporting Ratio (PRR), to identify potential safety signals. To assess whether the hemorrhage risk is higher with combination therapy compared to monotherapy, additive and multiplicative models were employed to evaluate the interactions between combination and single-agent treatments.ResultsThe combination of AGIs and ICIs significantly increased the risk of hemorrhagic adverse events, particularly tumor and pulmonary hemorrhage. Hemorrhagic events were common in females (50.97%) and older patients (aged 64+), frequently occurring within the first 30 days of treatment (38.11%). Gingival hemorrhage (ROR 3, PRR 418.9) and tumor hemorrhage (ROR 9.65, PRR 1893.36) were most common in the AGI group, while tumor hemorrhage (ROR 9.49, PRR 1350.78) and pulmonary hemorrhage (ROR 2.6, PRR 98.97) were prominent in the ICI group. In the combination group, esophageal variceal hemorrhage (ROR 40.72, PRR 2344.72) and tumor hemorrhage (ROR 19.31, PRR 1056.63) exhibited significantly increased risks Additive and multiplicative models indicated that the excess risk (RDAB = 0.01025, P<0.001) and relative risk (RRAB = 1.99277, P<0.001) of combination therapy were significantly higher than those of monotherapy, suggesting a positive interaction between the drugs that further increases the risk of hemorrhage.ConclusionOur study demonstrates that the combination of AGIs and ICIs significantly raises the risk of hemorrhage, underscoring the urgent need for enhanced monitoring protocols in clinical practice to improve treatment efficacy and safety.